Effect of Company Innovation on Sustainable Development: The Role of Strategic Management Accounting Information and Product’s Life Cycle - Namazi, Mohammad; Kazemi, Leila (Journal of Environmental Accounting and Management, 2026)
This study proposes a reflective ``latent multidimensional model" based on theories of sustainable development (SD), innovation, strategic management accounting (SMA), and companies’ product life cycle (PLC). The model is empirically tested by analyzing companies listed on the Tehran Stock Exchange, with SD disaggregated into its three pillars. Structural equation modeling, along with VAF and Sobel tests, are employed to evaluate the relationships. This research aim is to extend both theoretical and practical applications of corporate sustainability initiatives (CSI). Specifically, it explores the impact of CSI and the mediating role of SMA information on SD throughout the various PLC stages, testing these relationships empirically. The findings indicate that CSI has a significant effect on SD across the different stages of a company’s PLC. The least impact is observed at the maturity stage, while the most substantial effect occurs during the declining stage. Additionally, the mediating role of SMA information is significant only during the maturity and decline stages. Economic indicators such as cash flow from operations, operating profit, and economic value added are critical during the growth, maturity, and decline stages. These results have universal implications for academics, managers, and accountants across different countries, addressing economic, environmental, and social issues.